Antibiotics Resistance in Escherichia coli Isolated from Livestock in the Emirate of Abu Dhabi, UAE, 2014–2019 - Ghada Elderdiri Abdelwahab; Hassan Zackaria Ali Ishag; Zulaikha Mohamed Al Hammadi; Saeed Mohamed S Al Yammahi; Mohd Faoruk Bin Mohd Yusof; Muna Sayed Y. Al Yassi; Shaikha Saeed A. Al neyadi; Asma Mohammed A. Al Mansoori; Fawzia Hassan A. Al Hamadi; Ibtesam Abdullah S. Al Hamadi; Mohamed Ali Abdalla Al Hosani; Salama Suhail Mohammed Al Muhairi (International Journal of Microbiology)
Escherichia coli (E. coli) is a zoonotic pathogen that showed growing resistance to antibiotics. No descriptive analysis highlights the threat of antimicrobial-resistant (AMR) of E. coli among livestock in the United Arab Emirates (UAE). Herein, we conducted phenotypic and genotypic resistance studies on E. coli isolates from livestock samples in the Emirate of Abu Dhabi based on routine diagnosis between the periods 2014–2019. Bacterial culture and disk diffusion methods were used for bacterial isolation and phenotypic resistance analysis. Resistance mechanism was studied by PCR targeting the most commonly resistance genes: ampicillin (blaSHV, blaCMY, and blaTEM-1B), tetracyclines (tetA and tetB), co-trimoxazole [sulfamethoxazole (sul1, sul2, and sul3) + trimethoprim (dfrA1 and dfrA17)], aminoglycosides [aph(3'')-Ia, aph(6)-Id, and aac(3)-IV], and fluoroquinolones (qnrA and aac(6’)-Ib-cr). Analysis of 165 E. coli isolates showed resistant to ampicillin, tetracycline, co-trimoxazole, gentamicin, and enrofloxacin by 157/165 (95.4%), 154/165 (93.6%), 141/165 (86%), 139/165 (85%), and 135/165 (82.7%), respectively. Predominant resistance gene/s detected by PCR were blaCMY (119/160, 72%) and blaTEM-1B (154/160, 96.3%) for ampicillin; tetA (162/164, 98.8%) and tetB (112/164, 68.3%) for tetracyclines; sul2 (156/164, 95%), sul3 (138/164, 84%), and dfra17 (74/164, 44.5%) for co-trimoxazole; aph(3'')-Ia (134/164, 82.1%) and aph(6)-Id (161/164, 98.2%) for aminoglycosides; and aac(6’)-Ib-cr (61/61, 100%) for enrofloxacin. Both phenotypic and genotypic analyses revealed that all E. coli isolates were multidrug-resistant (resistance to 3, 4, and 5 antibiotics classes by 3.6%, 57.6%, and 38.8%, respectively) carrying one or more resistance gene/s for the same antibiotic. PCR profiling confirmed the presence of resistance genes corresponding to their antibiotic profile. Results of the study will highlight the knowledge based on E. coli AMR related to livestock in UAE that may call for interventions.